2003 IEEE Nuclear Science Symposium. Conference Record (IEEE Cat. No.03CH37515) 2003
DOI: 10.1109/nssmic.2003.1351863
|View full text |Cite
|
Sign up to set email alerts
|

Large area imaging detector for long-range, passive detection of fissile material

Abstract: Abstract--Recent events highlight the increased risk of a terrorist attack using either a nuclear or a radiological weapon. One of the key needs to counter such a threat is long-range detection of nuclear material. Theoretically, gamma-ray emissions from such material should allow passive detection to distances greater than 100 m. However, detection at this range has long been thought impractical due to fluctuating levels of natural background radiation. These fluctuations are the major source of uncertainty i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…These images are generated exactly as for the original proof-of-principle (POP) instrument [2]. In short, the linear location of the imager is determined by a Doppler fifth wheel mounted under the trailer.…”
Section: ) Single Imagermentioning
confidence: 99%
“…These images are generated exactly as for the original proof-of-principle (POP) instrument [2]. In short, the linear location of the imager is determined by a Doppler fifth wheel mounted under the trailer.…”
Section: ) Single Imagermentioning
confidence: 99%
“…The question of whether or not imaging information improves detection performance was addressed in [3] in the context of coded-aperture imaging systems. If the background intensity is known, reference [3] argued that imaging information does not improve the signal-to-noise ratio (SNR), therefore imaging information does not improve detection performance.…”
Section: Introductionmentioning
confidence: 99%
“…If the background intensity is known, reference [3] argued that imaging information does not improve the signal-to-noise ratio (SNR), therefore imaging information does not improve detection performance. However, if the background intensity is unknown, imaging may improve SNR [3] and thus detection performance by providing a means to separate the otherwise indistinguishable source and background photons. The analysis in this paper differs from that of [3] because we treat the problem from a detection task-based point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T has been shown that gamma-ray imaging allows one to overcome local background variations when searching for orphan sources [1,2]. Two methods of gamma-ray imaging that work at the energies of interest for this application (~50 -3000 keV) are Compton and coded-aperture imaging.…”
Section: Introductionmentioning
confidence: 99%